Report of the Joint Select Committee on the Condition of the Institution for the Deaf, Dumb and Blind (Senate doc. (North Carolina. General Assembly. Senate), 1852)
1852 Report of the Joint Select Committee on the Condition of the Institution for the Deaf, Dumb, and Blind. The committee was generally pleased, but recommended that $7,500 be allocated to build a principal's residence and additions to the main building, including the dormitories. Issued with a proposed bill to enact their recommendations.